Performance evaluation of a solar water heater integrated with a PCM nanocomposite TES at various inclinations - Al-Kayiem, H.H. (Elsevier Ltd, 2014)
The present work presents and analyzes the results acquired from outdoor experimental measurements of a flat plate solar collector integrated with built-in thermal energy storage. Paraffin wax as a PCM and a nanocomposite of paraffin wax with 1.0. wt of 20-nm nano-Cu particles were tested as the energy storage medium for TES. Three cases have been investigated, namely without PCM, with PCM, and with the Cu-PCM nanocomposite, at 10°, 20°, and 30° inclination angles of each case. The system performance was evaluated for water heating. The process involved a total change of the 60-l water tank at 7:00. PM and 7:00. AM. The use of water circulation of 0.5. kg/min and setting the collector at a 10° inclination angle was found to be the best operational condition. The measurement result of the tank water temperature at 7:00. AM, after 24. h of operation, was 35.1. °C when the system operated without TES, while the operation with the PCM and with the Cu-PCM nanocomposite resulted in 40.1. °C and 40.7. °C tank water temperatures, respectively. The best performances analyzed were at 10°, with efficiencies of 47.6, 51.1 and 52.0 for the cases without PCM, with PCM and with Cu-PCM nanocomposite, respectively. This indicates that the enhancement of the system using TES with paraffin wax is considerable, while further enhancement is not significant in the case of nanocomposite. Further measurements with various flow rates are recommended to investigate the performance of the developed solar-TES integrated system. © 2014 Elsevier Ltd.